Myron C. Taylor's Mission to the Vatican 1940–1950 - Conway, John S. (Church history, 1975)
The mission of Myron C. Taylor, personal representative of Presidents Roosevelt and Truman to Pope Pius XII, remains a strange anomaly in the history of the foreign relations of the United States. Ever since 1867, when an act of Congress terminated diplomatic relations between the republic and the world's oldest diplomatic entity, the United States had been unrepresented at the Vatican City. The short-lived attempt to reconstitute some form of permanent and effective diplomatic presence was born in controversy and lasted only from 1940 to 1950 during the incumbency of the single appointee. When on Taylor's resignation President Truman attempted to appoint a popular second world war general to the post, the outcry in the United States was so heated that the nomination had to be withdrawn and the venture abandoned. What went wrong? Was the storm of protest merely a result of religious bigotry on the part of American Protestantism? Or had Taylor's conduct of his mission been such as to evoke these outraged feelings? Certain episodes of the diplomatic negotiations between the United States and the Vatican have already been published, for example, the polite exchange of courtesies collected and introduced by Taylor himself, Wartime Correspondence between President Roosevelt and Pope Pius XII. Some more controversial matters, such as the question of the advisability of bombing Rome, were outlined from the American point of view in the Foreign Relations of the United States. Not until the Vatican's recent decision to publish some of its papers from the pontificate of Pius XII, or more particularly until the opening of Taylor's own papers in 1973, has it been possible to study in more detail the curious entanglement of theological, diplomatic and political considerations which governed the United States' relations with the Vatican, and encompassed Taylor's mission from beginning to end.